Comment on "Gone with the Wind: The Consequences of US Drone Strikes in Pakistan" - Joanne Haddad; Moritz Hennicke; Lamis Kattan; Thibault Lemaire; Marco Musumeci (Institute for Replication (I4R), 2023)
Mahmood and Jetter (2023) rely on daily wind conditions as an exogenous source of variation to assess the effects of 420 US drone strikes conducted in Pakistan from 2006 to 2016. The findings indicate that these drone strikes promote a subsequent surge in terrorism over the following days and weeks, contributing significantly to as much as 19% of all terrorist incidents and resulting in over 3,000 casualties in Pakistan during the specified period. In this comment, we successfully reproduce all the results from Mahmood and Jetter (2023), including tables and figures. We then conduct four sensitivity analyses to confirm the primary findings outlined in the original paper. We document the robustness of the main results in three out of four sensitivity checks, involving the omission of all controls across various specifications, utilization of the fixest package in R, and the inclusion of control variables determined through Lasso regressions. However, we show that the addition of year fixed effects substantially reduces the first-stage F-statistics and challenges the established negative relationship between wind gusts and drone strikes.
Keywords: 330